353 TEN-YEAR EXPERIENCE USING A RESPIRATORY THERAPIST-MANAGED, MDI-BASED PLAN FOR ACUTE ASTHMA ADMISSIONS AT A PEDIATRIC TERTIARY CARE CENTER. (1st January 2005) - Wood, M.; Schellhase, D.; Carroll, J.; Simmons, L.; Bylander, L.; Vargas, P.; Tilford, J.; Jones, S.
Abstract : Purpose: Pediatric acute asthma exacerbations requiring hospital admission account for six billion dollars spent and approximately 10 million school days missed annually in the US. This study aims to determine if an inpatient asthma care plan using respiratory therapists and MDI-based treatment is associated with improved asthma outcomes. Methods: To evaluate the efficacy of our inpatient asthma care plan (ACP), admissions for acute asthma identified by ICD-9 code were established for the fiscal years 1994 (FY94) through 2004 (FY04) using the hospital information system. Implementation of the ACP was in FY94 encompassing an acute care treatment algorithm, comprehensive education, and outpatient management and follow-up. The ACP uses MDI delivery of bronchodilator medications with registered respiratory therapist (RRT) administration and management. The ACP algorithm is based on an asthma severity index scored by the RRT at regular intervals during the hospitalization. Outcomes parameters included admission rates, emergency department visits, outpatient clinic visits, and asthma care charges. Results: Analysis of inpatient admissions for asthma indicates a reduction in the inpatient admissions by 58% from 287 in FY94 to 122 in FY04. Emergency department visits for asthma were reduced by 43% from 1, 469 in FY94 to 839 in FY04. Clinic visits for asthma increased by 35% from 2, 616 in FY94 to 4, 007 in FY04. Total charges for asthma visits were compared by adjusting FY94 charges to 2004 dollars using the medical care component of the consumer price index. Adjusted charges in FY94 were 3, 581, 238 compared to charges of 4, 275, 576 in FY04. Conclusions: A RRT managed, MDI-based ACP is an effective means of managing acute asthma in the inpatient setting. The increased number of visits in the outpatient clinic over the study period suggests improved follow-up from hospitalizations and a shift toward outpatient care. Total charges for all asthma visits increased during the 10-year period, likely reflecting escalating costs of medical care, asthma medications and other medical factors.